Understanding the socio-economic contributions of different wildlife ranching business models in South Africa - Denner, Candice (Department of Biological Sciences, 2023)
Amidst the biodiversity loss crisis, the expansion of wildlife ranching has been associated with a numerous conservation benefits and linked to job creation and substantial economic contributions. However, an understanding of the socio-economic contributions of wildlife ranching that account for the heterogeneity and diverse business strategies within the wildlife economy remains limited. The aim of this research was to determine some of the socio-economic contributions of different wildlife-based business models, as defined by their main revenue-generating activities, within the wildlife ranching industry in South Africa, as well as the financial sustainability of these business models and their contributions. In total, 268 owners and managers of privately-owned wildlife ranches and agricultural farms (for comparative purposes) in the Eastern Cape and Limpopo provinces of South Africa were surveyed. Through these surveys, I collected data on the revenue-generating activities they rely on, differences in their financial metrics, the number of jobs they provided and the salaries and non-salary benefits their employees received. This data was based on a non pandemic year (2019/2020) and a post-Covid-19 pandemic year (2021/2022) to assess the sustainability of ranches in response to a large-scale threat. Through a hierarchical clustering analysis of revenue-generating activities, six business models within the wildlife ranching sector were delineated according to their primary focus: ecotourism, trophy hunting, mixed hunting (i.e., biltong and trophy), mixed wildlife-agriculture, wildlife breeding and trophy hunting-game meat business models. On average, trophy hunting and ecotourism focused business models were found to make greater economic contributions, through high upfront capital investment and operating expenditure, than the mixed wildlife-agriculture and mixed hunting focused models. Ecotourism focused ranches employed more people than all business models except trophy hunting. They also provided higher quality jobs (defined as jobs that increase job security, workplace equality, and job satisfaction through higher compensation) by employing the highest proportion of women (41% on average) and the highest proportion of skilled employees (45% on average) across business models, including when compared with conventional agriculture. Trophy hunting focused ranches also employed more people per hectare than other models (although on average, over a quarter of these jobs are seasonal). They also offer the greatest variety of non-salary benefit types to employees (particularly in the form of housing and food), along with mixed hunting ranches. Trophy hunting ranches are considerably more profitable than ecotourism and wildlife breeding ranches, though there was high variability within the ecotourism model, likely as a result of some being focused on high-end ecotourism, and others on low-end ecotourism. After Covid-19, all business models experienced lower profitability and some enterprises across all business models retrenched employees. On average, the mixed-activity models did not retrench employees post-pandemic. Those that fared better during Covid-19 had more diversified profiles of revenue-generating activities (i.e., the mixed activity models), suggesting that enabling this diversity of approaches is important for the sustainability of wildlife ranching. The evidence presented here advances our understanding of the heterogeneous impacts and responses of wildlife ranches and suggests that differences in the socio-economic contributions of these ranches should be considered across business models as several distinctions exist between these models. A more nuanced approach to understanding the socio-economic contributions of wildlife ranching will benefit the policy discourse surrounding the industry by providing information relevant to specific business models', which may lead to more effective policy implementation and improve the industry's sustainability and growth.